PERAN MEDIASI MOTIVASI INTRINSIK PADA KINERJA DOSEN - Avni Dewi Sinurat; Pahlawansjah Harahap; Yuli Budiati (LPPM STIE Muhammadiah Bandung, 2025)
The decline in the performance of permanent lecturers at the Nalanda Institute prompted this research. The aim of this study is to examine the influence of job training and work discipline on the performance of permanent lecturers at the Nalanda Institute, by placing intrinsic motivation as a variable that acts as an intermediary. This research was conducted quantitatively, and data was collected using a questionnaire based on a 5-point Likert scale, while data were processed using multiple linear regression analysis using SPSS 27. The sampling method uses the saturated or census sampling method, in which the entire population was used as the research sample due to its relatively small size. The sample consisted of 41 permanent lecturers at the Nalanda Institute. The findings of this study indicate that that job training, work discipline, and intrinsic motivation have a positive and significant influence on the performance of permanent lecturers at the Nalanda Institute. Job training, work discipline, and intrinsic motivation also have a positive and significant influence on the intrinsic motivation of permanent lecturers. Intrinsic motivation is also able to mediate the relationship between job training and work discipline and the performance of permanent lecturers.Keywords: Job training; work discipline; intrinsic motivation; performance of permanent lecturers.